A simplified damage-following model for reinforced concrete columns - Nuno Pereira (2014)
Nonlinear models are becoming a widely solution for seismic evaluation and design of new structures. The implementation of those models in engineering practice requires robust methodologies and guidelines about the consistent use of nonlinear analysis. Objective numerical models must be developed or, at least, the extent of the accuracy of each possible solution must be accounted for and its impact included within the safety verification framework. One particular issue that affects distributed inelasticity models is the consistency of the numerical model adopted. Not only is an analyst interested in global performance engineering demand parameters but also code-based procedures require that local response should be used in the assessment stage. Hence, it is important to reconcile local (Moment-curvature) and global (Force-drift) responses. The simplified damage-following models presented herein try to circumvent some issues associated with objectivity and user-dependent model selection. The considered models ensure correct capture of hardening behavior ranges and an objective response during softening. This is done by updating at each analysis step the inelastic zone length. A simple application is considered comparing experimental results from 1 RC column and regularized beam models available in OpenSees.